Learning Vector Quantization Pada Pengenalan Pola Tandatangan - Mubarika, Sofia; Munir, M.; Firdausi, Ketut Sofjan; Widarto, Widarto (JURNAL SAINS DAN MATEMATIKA, 2006)
ABSTRACT---In this paper, we analyze and compute distribution of thermal neutron flux in core of Kartiniâ€™s Reactor using â€œSwadayaâ€ detector, both for axial (function of z) and radial (function r) direction. First, â€œSwadayaâ€ detector is calibrated by activation plate method, which the output from detector is current. The result of calibration is thermal neutron flux (Ñ„) dependent on current (I) that can be written as Ñ„ = 4,57x1020I - 2,74x1011. Distribution for neutron thermal flux for axial direction and radial direction respectively Ð¤ = 5,10 x 1012 + 5,99 x 1013 and Ñ„ = 1.08 x 1012 + 1,00 x 103 which in reactor core Ñ„ has largest value in center position for radial direction. Â  Keywords: flux neutron distribution, nucleus reactor, Swadaya detector